Metallicity evolution of direct collapse black hole hosts: CR7 as a case study - Agarwal, Bhaskar; Pellegrini, Eric William; Klessen, Ralf S. (Monthly notices of the Royal Astronomical Society, 2017)
In this study, we focus on the z ∼ 6.6 Lyman α CR7 consisting of clump A, which is host to a potential direct collapse black hole (DCBH), and two metal-enriched star-forming clumps B and C. In contrast to claims that signatures of metals rule out the existence of DCBHs, we show that metal pollution of A from star-forming clumps B and C is inevitable, and that A can form a DCBH well before its metallicity exceeds the critical threshold of $$10^{-5}\text{--}10^{-6}\ \rm Z_{{\odot }}$$. Assuming that metal mixing happens instantaneously, we derive the metallicity of A based on the star formation history of B and C. We find that treating a final accreting BH of 106-107 M⊙ in A for nebular emission already pushes its H160 − [3.6] and [3.6] − [4.5] colours into the 3σ limit of observations. Hence, we show that the presence of metals in DCBH hosts is inevitable, and that it is the coevolution of the Lyman-Werner radiation field and metals originating from neighbouring galaxies that governs DCBH formation in neighbouring initially pristine atomic cooling haloes.